Diversity and Nutritional Values of Wild Edible Leaves of Acholi Sub-region, Northern Uganda - Loki, Robert B. O.; Ndyomugyenyi, Elly K. (Age, 2016)
Over the past years, there has been increase in the consumption of wild food plants. A study was conducted in the districts of Gulu, Kitgum, Pader and Amuru to establish the diversity and nutritional value of Wild Edible Leaves (WEL) for human consumption. Epistemology of consumption of the WEL plant species was also assessed. A total of 206 respondents, which included formerly abducted children (FAC) and district officials were recruited for the study in two sub-counties from each district. Data were collected using structured questionnaires, Laboratory analysis, observations and focus group discussions. Secondary sources of data were also reviewed. Most respondents who had knowledge, collected and consumed wild leaves were adults between 40-49 years and had little formal education. Eighteen wild edible leave plants species belonging to 14 families were recorded with forest, forest gaps and forest edge habitat as well as grassland registering 28% for each of the habitat of the WLP species as water habitat presenting the least number (2%) of WLP species. Most wild edible leave plant species were richer in vitamin C (>0.34 x 102 mg/100g) and sugar (>4.45%). Although Commelina rumelica was poorer in Sugar (1.25%) but it recorded the highest iron (3.66mg/100g). Highest amount of Phosphorus was recorded for the all the species analysed with Lathyrus tuberosus recoding the highest (66.09mg/100g). Fat was lowest throughout the species analysed with Lathyrus tuberosus recording highest (2.31mg/100g) and Commelina rumelica registering the lowest fat content (0.67mg/100g). The knowledge of wild leaves consumption was mainly informal, acquired from the parents, grandparents and friends. However, 19.4% of respondents were influenced to eat the leaves either by hunger or rebel commanders during food shortage. The knowledge and consumption of WEL are gradually increasing in contrast to the wake of increasing improved agricultural production technology and marketed food plants, eroded culture and tradition. There is need for thorough nutritional evaluation prior to recommendation of WEL for large scale consumption and marketing
Keywords: Consumption, Nutritional values, Epistemology, diet, food security, Wild Edible Leaves